2018
DOI: 10.1002/hep.29918
|View full text |Cite
|
Sign up to set email alerts
|

12 Weeks of a Ribavirin‐Free Sofosbuvir and Nonstructural Protein 5A Inhibitor Regimen Is Enough to Treat Recurrence of Hepatitis C After Liver Transplantation

Abstract: SOF + NS5A inhibitors without RBV for 12 weeks constituted reliable therapy for recurrent HCV post-LT with an excellent SVR12 whatever the fibrosis stage, HCV genotype, and previous HCV treatment. (Hepatology 2018; 00:000-000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The CUPILT prospective cohort study enrolled transplanted patients with HCV-recurrence benefiting from second generation DAAs from 2013 to 2015 and found that these treatments were highly effective in LT patients, including those with severe HCV recurrence [11][12][13]. More specifically, we reported that sofosbuvir-based therapy could lead to virological eradication, clinical and biological improvement in most patients with FCH following LT with very good tolerance [14].…”
Section: Introductionmentioning
confidence: 91%
“…The CUPILT prospective cohort study enrolled transplanted patients with HCV-recurrence benefiting from second generation DAAs from 2013 to 2015 and found that these treatments were highly effective in LT patients, including those with severe HCV recurrence [11][12][13]. More specifically, we reported that sofosbuvir-based therapy could lead to virological eradication, clinical and biological improvement in most patients with FCH following LT with very good tolerance [14].…”
Section: Introductionmentioning
confidence: 91%
“…36,38 Six studies have reported the efficacy of DAA combination regime for post-LT setting from 2018 to 2019 (Table 3). [39][40][41][42][43][44] Along with these successful DAA treatments, a couple of considerations were reported. Erard et al 45 HCV co-infection within the early phase (4-8 weeks) of DAA treatment.…”
Section: Hepatitis B Virus/hepatitis C Virusmentioning
confidence: 99%
“…Furthermore, the survival of LT recipients with HCV‐related liver disease has clearly improved because of treatment for HCV recurrence, which is a common problem in clinical practice . Six studies have reported the efficacy of DAA combination regime for post‐LT setting from 2018 to 2019 (Table ) …”
Section: Hepatitis B Virus/hepatitis C Virusmentioning
confidence: 99%